Experimental substantiation of teaching algorithm of technique in weightlifting and powerlifting competitive exercises - Tovstonoh, O.; Roztorhui, M.; Zahura, F.; Vynogradsky, B. (Journal of Physical Education and Sport, 2015)
Fundamentals of teaching the competitive exercises technique in strength sports need to be improved to meet the requirements of sports practice. The research aim is to find out the effectiveness of algorithmization of teaching the competitive exercises technique in strength sports on the example of weightlifting and powerlifting.It has been established that athletes of experimental groups made significantly (p.0,05) fewer errors as compared to control groups athletes. Algorithmization of teaching the technique in strength sports contributed to the quality of mastering the competitive exercises technique by athletes at the stage of initial training as compared to the training program of junior sport schools.